Work effectiveness of regional inspectorate employees of Riau Islands Province with the determination of digital transformation, self-efficacy and innovative behaviour through work motivation - Syafrizal, Syafrizal; Wibisono, Chablullah; Nurhatisyah, Nurhatisyah (Goodwood Publishing, 2023)
Purpose: This study aimed to examine the influence of digital transformation, self-efficacy, and innovative behavior on the work effectiveness of employees in the Riau Islands Provincial Inspectorate, with work motivation analyzed as an intervening variable. Research Methodology: The sample in this study comprised employees of the Riau Islands Provincial Inspectorate. A total of samples used was 103 respondents were included in the study. The obtained data were analyzed using data analysis techniques with the help of AMOS 24.0. Results: The findings show that digital transformation, self-efficacy, and innovative behavior significantly affect work effectiveness. Self-efficacy significantly affected work motivation, whereas digital transformation and innovative behavior did not. Work motivation has a strong and significant influence on work effectiveness. Moreover, self-efficacy indirectly affects work effectiveness through work motivation, whereas digital transformation and innovative behavior show no significant indirect effects via motivation. Conclusions: This study concludes that self-efficacy and motivation are critical drivers of employee effectiveness, whereas digital transformation and innovation require stronger organizational support to contribute effectively. Limitations: The study was limited to one government institution, reducing generalizability, and relied on self-reported survey data that may contain biases. Contribution: This study contributes theoretically by clarifying the mediating role of motivation and practically by offering insights for public sector agencies to strengthen digital transformation initiatives, improve employee confidence, and encourage innovation.